2017
DOI: 10.1523/jneurosci.1787-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Deletion of the L-Type Calcium Channel Cav1.2 in NG2-Positive Cells Impairs Remyelination in Mice

Abstract: Exploring the molecular mechanisms that drive the maturation of oligodendrocyte progenitor cells (OPCs) during the remyelination process is essential to developing new therapeutic tools to intervene in demyelinating diseases such as multiple sclerosis. To determine whether L-type voltage-gated calcium channels (L-VGCCs) are required for OPC development during remyelination, we generated an inducible conditional knock-out mouse in which the L-VGCC isoform Cav1.2 was deleted in NG2-positive OPCs (Cav1.2). Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…Consistent with this finding, the deletion of CaV1.2 from adult OPCs was reported to reduce their capacity to remyelinate the corpus callosum following cuprizone-induced demyelination (Santiago González et al, 2017), suggesting that CaV1.2 can, at least following an injury, regulate adult OPC function. However, it is also possible that CaV1.2 may differentially regulate developmental versus adult OPCs or OPCs in the healthy versus injured CNS.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Consistent with this finding, the deletion of CaV1.2 from adult OPCs was reported to reduce their capacity to remyelinate the corpus callosum following cuprizone-induced demyelination (Santiago González et al, 2017), suggesting that CaV1.2 can, at least following an injury, regulate adult OPC function. However, it is also possible that CaV1.2 may differentially regulate developmental versus adult OPCs or OPCs in the healthy versus injured CNS.…”
Section: Introductionsupporting
confidence: 59%
“…While it is unclear how callosal OPC inputs and signaling can change with aging, it is interesting to note that demyelination restores neuron‐OPC synaptic communication in the rat caudal cerebellar peduncle (Gautier et al, ) and causes adult OPCs in the corpus callosum to revert to a transcriptional state similar to that of developmental OPCs (Moyon et al, ). Such changes could account for CaV1.2 having no effect on adult myelination in the healthy adult mouse brain but acting to expedite or enhance remyelination of the corpus callosum following cuprizone‐induced demyelination (Santiago González et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, several ion channels have already been shown to be relevant for the initiation or regulation of basal oligodendroglial cell functions (proliferation, migration and differentiation). In this context, voltage‐gated Ca 2+ entry (via Ca V 1.2 channels) has not only been shown to promote oligodendrocyte maturation and myelination in vitro (Cheli, Santiago Gonzalez, Spreuer, & Paez, ) but also to be crucial for remyelination in the cuprizone model (Santiago Gonzalez et al, ). Also, Ca 2+ ‐release from internal stores seems to be involved in mechanisms of oligodendrocyte differentiation (Li et al, ; Weider et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Protein samples were extracted using lysis buffer as described by Santiago González et al (2017). Twenty mg of proteins were separated with NuPAGE Novex 4-2% Bis-Tris Protein Gels (Life Technologies) and electro-blotted onto PVDF membranes.…”
Section: Western Blotmentioning
confidence: 99%
“…Removal of exon 2 leads to a truncated, non-functional protein. Conditional Cav1.2 deletion in cortical and hippocampal neurons as well as immature oligodendrocytes has been successfully generated in previous experiments (Cheli et al, 2016b;Santiago González et al, 2017). The GFAPCreER T2 transgenic line expresses a tamoxifen-inducible Cre recombinase under the control of the human GFAP promoter (Hirrlinger et al, 2006).…”
Section: Ablation Of Cav12 Channels In Gfap-positive Astrocytes Attementioning
confidence: 99%